The human factor in the functioning of "Lean Thinking" - Safronova Kseniia Olegovna (Sovremennye Tehnologii Upravleniâ, 2013)
This article includes the analyses of influence the «Lean Production» conception. Top – manager should any his decision to employees of company and gets the feedback. The successful companies understand the importance with the employee’s communication. The staff is the main active of organization, and that is why, the top – management should direct actions on the education loyal employee and the creation of a corporate (team) spirit. The staff is the «thinking» enterprises active, but not the mechanism of achieving goal. Company come the «thinking» following the management principles of the «Lean Production» conception. The article includes correlation between of the management style and methodology as management mechanism of business organization. Also «Deming Cycle» and «Triangle of Joiner» like a method of in-house training programs (education) in the company.